2010
DOI: 10.1080/00140130903402242
|View full text |Cite
|
Sign up to set email alerts
|

Effects of horizontal whole-body vibration and standing posture on activity interference

Abstract: Standing people are exposed to whole-body vibration in many environments. This paper investigates the effects of horizontal whole-body vibration and standing posture on task performance. Sixteen participants were exposed to random vibration (up to 4Hz), whilst performing a timed pegboard task in two standing postures. Objective and subjective indicators of performance were used. Time taken to complete the task increased progressively with increases in vibration magnitude; the fore-and-aft posture generally sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…In congruence with previous MII research (e.g., Baker & Mansfield, 2010;Brown et al, 2001), this study shows that MII occurrence increases by increasing peak sway acceleration consistently in all motion conditions.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In congruence with previous MII research (e.g., Baker & Mansfield, 2010;Brown et al, 2001), this study shows that MII occurrence increases by increasing peak sway acceleration consistently in all motion conditions.…”
Section: Discussionsupporting
confidence: 76%
“…These motion parameters are comparable to what is found in vessels like the FFG-7 frigate (Morrison, Dobie, Willems, Webb, & Endler, 1991) or in earlier MII research (Crossland & Lloyd, 1993). The duration of the motion session, approximately one hour, is comparable to that used in earlier MII research (Baker & Mansfield, 2010;Crossland & Lloyd, 1993;Crossland & Rich, 1998). …”
Section: External Validity Of Motion Profilesmentioning
confidence: 51%
See 1 more Smart Citation
“… Elton and Nicole (2013) found that an everyday cold temperature of 5°C had a significant effect on older adults' ability to carry out fine finger tasks and product interactions;  Baker and Mansfield (2010) reported decrements in dexterity when participants were exposed to vibration which could be experienced on public transport; Hopkinson and Collins (1970) reported that the human eye can detect detail ten times as fine in daylight as it can under starlight.…”
Section: And Hadrian (Human Anthropometric Datamentioning
confidence: 99%
“…When the horizontal WBV was applied while the participants stood with their feet apart, the horizontal vibration caused an antero-posterior weight bearing (Baker & Mansfield, 2010;Griffin & Hayward, 1994), and an increase in muscle activity to maintain the position, which exerted positive effects on the improvement of stability. Likewise, the horizontal WBV may have positive effects on the body, including muscle activation.…”
Section: Introductionmentioning
confidence: 99%